2001
DOI: 10.1115/1.1398290
|View full text |Cite
|
Sign up to set email alerts
|

Contact Vibration of Micro-Textured Sliders

Abstract: We have formed a micro-texture on a pico-slider’s air-bearing surface to reduce the vibration when the slider comes into contact with the disk. The contact between slider and disk was controlled by adjusting the ‘interference height.’ Our measurements show that, at a giving interference height there is a significant less vibration in the textured slider. This lower amplitude of vibration is attributed to the lower friction force, which is in turn due to the smaller area of contact. We have also introduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Our results showed that even completely filled dimples can have a positive hydrodynamic effect if a preferred adherence of wear particles at the dimples results in the formation of bumps. Such a reversed microtexturing was successfully used in hard disc drives [16,17]. The third effect often postulated in literature is the storing of lubricant in the dimples (secondary lubrication effect) [7,18,19].…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that even completely filled dimples can have a positive hydrodynamic effect if a preferred adherence of wear particles at the dimples results in the formation of bumps. Such a reversed microtexturing was successfully used in hard disc drives [16,17]. The third effect often postulated in literature is the storing of lubricant in the dimples (secondary lubrication effect) [7,18,19].…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al fabricated micro-textured sliders by ion-etching, and reported that the amplitude of the slider vibration is strongly related to the real area of contact at the HDI (Xu and Tokisue 2002). The results showed that a textured slider is effective to reduce friction force.…”
Section: Introductionmentioning
confidence: 90%
“…3.2 Slider with controlled texture/roughness Xu et al (2002) found that a micro-textured slider could reduce the vibration from contact because of its low frictional force. We speculated that a textured slider could also effectively decrease intermolecuar force from the head disk interface acting on the ABS.…”
Section: Effect Of Roughness On Intermolecular Forcementioning
confidence: 99%
“…Xu et al (2002) found that a microtextured slider could reduce the vibration due to contact because of its low frictional force. Zhang et al (2005) recently discovered that texturing could be used to reduce the effect of intermolecular forces.…”
Section: Introductionmentioning
confidence: 98%